CSF and Serum Biomarkers of Cerebral Damage in Autoimmune Epilepsy - Nass, Robert Daniel; Akgün, Katja; Dague, Karmele Olaciregui; Elger, Christian Erich; Reichmann, Heinz; Ziemssen, Tjalf; Surges, Rainer (Frontiers in Neurology, 2021)
Introduction: Our goal was to investigate whether biomarkers of cerebral damage are found in autoimmune mediated epilepsy (AIE) and whether these can differentiate AIE from other seizure disorders. Methods: We retrospectively searched our CSF database for patients with definite AIE, hippocampal sclerosis due to other causes (HS), idiopathic generalized epilepsy (IGE) and psychogenic, non-epileptic seizures (PNES). We measured serum and CSF Tau, neurofilament 1 (NFL), glial fibrillary acid protein (GFAP) and ubiquitin-carboxy-terminal hydrolase L1 (UCHL1) with a single molecule array. Results: We identified suitable samples from patients with AIE (n = 13) with different antibodies and compared them to HS (n=13), IGE (n=7) and PNES (n=8). NFL levels were significantly elevated in serum (p=0.0009) and CSF (p < 0.0019) of AIE patients. The AIE group was significantly older, while the disease duration was significantly shorter than in the control groups. NFL correlated significantly with age in all groups and NFL levels of AIE patients were hardly higher than those of healthy elderly people published elsewhere. Conclusions: Our data indicate that elevated NFL-levels in AIE patients are most likely to be due to the higher age in this group and not due to the underlying inflammation. Only if larger, prospective studies with intraindividual, longitudinal analyses and treatment responses would contradict our findings, NFL in serum might yet become a biomarker for disease activity and differential diagnosis.